CHALLENGES AND OPPORTUNITIES OF INDONESIAN AUTHORS FOR PUBLISHING ARTICLES IN ENGLISH JOURNALS: A MICROSTRUCTURE STUDY IN IHLRAMS - Warsidi, Warsidi (UC Journal: ELT, Linguistics and Literature Journal, 2025)
The number of generic microstructure studies within English research articles (RAs) has recently increased worldwide. However, studies on this area in the Indonesian context are still limited, specifically in the method section. To address this need, in this paper, the researcher focuses on analyzing the microstructure of 30 Indonesian History and Law Research Article Methods (IHLRAMs) because these two disciplines have never been investigated earlier in the Indonesian context. For the analysis, an English model found by Zhang and Wannaruk (2016) was employed for the initial analytical framework in both corpora. However, both data sets only partially employ this English model; thus, further analysis employed a top-down approach. The results showed that the corpora have their own microstructure models, called Indonesian history research article methods (IHRAMs) and Indonesian law research article methods (ILRAMs) models. These two findings models imply that the microstructure of the Indonesian history and law RAMs is different from an English model. Thus, these differences become a challenge for Indonesian authors and possibly also those whose English is their foreign language (EFL) when they want to publish articles in English journals. On the other hand, comprehending these differences may improve their awareness, as well as their opportunities for publishing RAs in English journals.